ASSOCIATION OF LIPID FRACTIONS LEVELS WITH CARDIOVASCULAR DISEASE - Rada, Feryal H (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The aim of this study is to analyze the association of serum lipids and lipoproteins in patients with angina pectoris. Methods: A total of 110 patients (60 males and 50 females) with angina pectoris aged (55Â±5) years and 80 healthy controls (43 males and 37 females) aged (45Â±4) years were enrolled in this case-control study from the clinic of Al Yarmouk Hospital. Serum lipids, lipoprotein(a) [Lp(a)], apolipoprotein-A1, and apolipoprotein-B levels were measured and studied. Results: The results of this study showed that increased odds of angina pectoris were associated with increased serum levels of Lp(a) more than serum levels of apolipoprotein-B. Conclusions: Analysis of Lp(a) may be an important determinant of cardiovascular disease diagnosis. Keywords: Lipoprotein(a), Apolipoprotein-A1, Apo lipoprotein-B, Angina pectoris.